Experiential learning model with mind mapping on fungi: how to improve science process skills? - Desi Indriani; Ixora Sartika Mercuriani (Universitas Negeri Jakarta, 2019)
This research aimed to find out the effectiveness of experiential learning (EL) model with mind mapping to improve the science process skills (SPS) on fungi materials. It was quasi-experiment research by using pre-test post-test control group design. The population of the study was all of the tenth-grade students of Kalasan State 1 Senior High School amount of 127 students in the odd semester in 2018/2019 of the school year. Sample techniques were cluster random sampling. The sample consisted of 26 students (10 students male and 16 students female) as the experiment class by implementing EL model with mind mapping and 26 students (9 students male and 17 students female) as control class by using 5M (observing, asking, collecting, associating, communicating) learning model. The used instrument was ten essay questions. The data of the research were analyzed by using t-test (independent sample t-test). Based on the result of the normalized gain score, it showed that there was an improve of SPS about 0,85 in the experiment class higher than that in the control class about 0,70. Besides, it also showed a significant value (2-tailed) that was 0,000 (<0,05). It meant that there was a difference in science process skills between the experiment class and control class, so the learning process through EL learning model with mind mapping proved useful to improve the students’ science process skills.